Fuzzy Controlled Routing in a Swarm Robotic Network - Navya Manoj (Institute of Advanced Engineering and Science, 2014)
Swarm Robotics originated in the research inspired by biology. It is the usual sense of the multi-robot systems which have been given the emerging attributes of swarm intelligence. In nature, ants, termites, wasps, bees and other social insects have inspired surprisingly inspiration of human. These groups of organisms show how to interact with a large number of simple individuals and generate the collective intelligence of systems to cope with complicated tasks. Swarm Robotics is a special robot system which is composed of a group of indiscriminate robots and so it is a typical distributed system. If a task is for only one robot and the robot will be very complex and expensive inefficiently. But if it is for the swarm robotics, the complex task can be done by many more simple robots efficiently. For the Routing problem, the quality of a potential route is determined by the length of the route (i.e. number of links) and the congestion along the route. It is desired to balance the traffic load among links in the network so it is desirable to select routes with a low obstacle rate. In addition, shorter routes are preferred over longer routes because they use fewer network resources